Collaborative Governance dalam Pengawasan Angkutan Barang Umum yang Berkontribusi terhadap Program Zero Over Dimension dan Over Loading - R. Harryawan Latullah; Galih Adi Sulistyo; Maudhy Satyadharma; Hado, Hado (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The Zero Over-Dimension and Over-Loading (ODOL) program is a strategic government effort to improve transportation safety and maintain the sustainability of road infrastructure. However, the effectiveness of its implementation depends heavily on cross-agency synergy and the participation of various stakeholders. This article analyzes the role of collaborative governance in strengthening oversight of public freight transportation to align with the Zero ODOL goal. This research employed a qualitative method, with informants selected purposively, considering their understanding of the challenges posed by the local government in promoting air connectivity in Southeast Sulawesi Province. The research was conducted from August to November 2025. The results concluded that effective oversight of public freight transportation is key to the success of the Zero Over-Dimension and Over-Loading program in maintaining safety and infrastructure sustainability. Collaborative governance, as a multi-stakeholder governance model, provides a strategic solution to address the complexity of oversight.